Optimized Design of Francis Turbine Runner for Sand Laden Water - Shrestha, Krishna Prasad; Thapa, Bhola; Dahlhaug, Ole G.; Neupane, Hari Prasad; Gurung, Nikhel; Kayastha, Aatma Ram (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Nepal has an enormous amount of water resources and the topography gives rise to a huge hydropower potential. Out of 83,000 MW, only about 43,000 MW is economically and technically feasible. However, rivers of Nepal contain heavy quantities of sand particles. This is why the hydropower plants of this region face severe sand erosion problem.      Erosion mechanism in hydropower is a complex phenomenon. It is a major technological challenge for R-O-R (Run off river) hydropower plants. There are several technologies to reduce erosion but none of them has proven to be economically viable. The hydraulic design of the turbine with a new design philosophy expected to reduce sand erosion considerably and this process is economic too. This paper describes the alternative optimized design of Francis turbine runner for large sediment load. The process involves optimization to obtain specific Francis runner blade using not defined ANSYS CFX parametric study. The process also includes analysis of the runner blade using CFX parametric study and Fluid structure interaction simulation for specific blade design. Design and drafting of the runner and part model design for FSI (Fluid Structure Interaction) analysis have also been described.DOI: http://dx.doi.org/10.3126/hn.v13i0.10038HYDRO NEPAL Journal of Water, Energy and EnvironmentIssue No. 13, July 2013Page: 36-43Uploaded date: 3/13/2014